The Prevalence and Impact of Dental Anxiety Among Adult New Zealanders - Ishani Sukumaran; Shay Taylor; W. Murray Thomson (Elsevier, 2021)
Objective: To describe the prevalence and impact of dental anxiety in the New Zealand adult population. Methods: Secondary analysis of data from the 2009 New Zealand national oral health survey. Dental anxiety was measured using the Dental Anxiety Scale (DAS). Results: The prevalence of dental anxiety was 13.3% (95% CI = 11.4, 15.6). On average, DAS scores were higher by 14% among females, lower among those in the oldest age group (55+), higher by 10% among those in the European/Other ethnic category, and higher by 10% among those residing in the most deprived neighbourhoods. Those who were dentally anxious had greater oral disease experience and were less likely to have visited a dentist within the previous 12 months. They also had poorer oral health-related quality of life, with the highest prevalence of OHIP-14 impacts observed in dentally anxious 35- to 54-year-olds. Conclusions: Dental anxiety is a dental public health problem. It is an important contributor to poor oral health and care avoidance among New Zealanders. There is a need to develop both clinical and population-level interventions aimed at reducing the condition's prevalence and impact.